Optoelectronical properties of polycrystalline ?-GaSe thin films - Qasrawi, AF; Ahmad, MMS (Wiley-V C H Verlag Gmbh, 2006)
Polycrystalline beta-GaSe thin films were obtained by the thermal evaporation of GaSe crystals onto glass substrates kept at 300 degrees C under a pressure of 10(-5) Torr. The transmittance and reflectance of these films was measured in the incident photon energy range of 1.1-3.70 eV. The absorption coefficient spectral analysis in the sharp absorption region revealed a direct allowed transitions band gap of 1.83 eV. The data analysis allowed the identification of the dispersive optical parameters by calculating the refractive index in the wavelength region of 620-1100 nm. In addition, the photocurrent of the samples was studied as function of incident illumination-intensity and temperature. The photocurrent is found to exhibit sublinear and supralinear character above and below 270 K, respectively. The temperature dependent photocurrent data analysis allowed the calculation of photocurrent activation energies as 603, 119 and 45 meV being dominant in the temperature regions of 250-300 K, 180-240 K and 80-160 K, respectively. (c) 2006 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: GaSe; thin film; optical; refractive index; photoconductivity; recombination